Study of the Quantitative Structure of True Mangroves Present in the Mangal forests of Tellicherry, Pappinissery and Kunhimangalam of Kannur District - Khaleel, K. M. (Indian Forester, 2005)
Quantitative structure of the true mangroves was studied in terms of Frequency, Density and Abundance. Compared to the Sunderbans of West Bengal, Kerala has a very few areas of Mangrove forest. It was estimated that out of the 17 km2 of Mangroves of Kerala, a major share is present in Kannur District. Mangroves form a special type of ecotone, which is significant in the conservation and protection of wetlands. The present study aims to make a quantitative analysis of the different species present in three sample sites viz., Tellicherry, Pappinissery and Kunhimangalam of Kannur District. It is observed that most of the Mangroves present in these regions is in the threat of destruction as they are under private ownership. Each sample plot is characterized by the presence of a particular dominant species and its combinations. Tellicherry is characterized by Avicennia-Sonneratia-Rhizophora combination, while Pappinissery has Kandelia-Avicennia-Aegiceras group and Kunhimangalam shows ExcoecariaAvicennia-Rhizophora-Bruguiera belt. Out of the 12 species of true Mangrove plants observed, 5 are in common occurrence in most of the places while 3 species are very rare. Abundant species diversity is found in the Kunhimangalam belt. 25 species of Mangrove associates are also observed in these regions.